The sentinels of coronary artery disease: heterogeneous monocytes - Chen, Yanyu; Luo, Daya; Gao, Renzhuo; Wu, Jinjing; Qiu, Xingpeng; Zou, Yang; Jian, Yingchao; Zhang, Shuhua (Frontiers in Immunology, 2025)
Monocytes are heterogeneous immune cells that play a crucial role in the inflammatory response during atherosclerosis, influencing the progression and outcome of the disease. In the pathogenesis of atherosclerotic diseases, such as coronary artery disease (CAD), monocytes not only serve as the initial sensors of endogenous and exogenous pathogenic factors, but also function as intermediators that bridge the circulatory system and localized lesions. In the bloodstream, heterogeneous monocytes, acting as sentinels, are rapidly recruited to atherosclerotic lesions, where they exhibit a heightened capacity to respond to various pathological stimuli upon detecting signals from damaged vascular endothelial cells. Clinical studies have demonstrated that the heterogeneity of monocytes in CAD patients presents both diversity and complexity, varying across different disease subtypes and pathological stages. This review explores the heterogeneity of monocytes in CAD, focusing on alterations in monocyte subset numbers, proportions, and the expression of functional receptors, as well as their correlations with clinical features. Additionally, we propose strategies to enhance the clinical utility value of monocyte heterogeneity and outline future research directions in the field of CAD. With the widespread application of high-parameter flow cytometry and single-cell sequencing technologies, it is anticipated that a comprehensive understanding of monocyte heterogeneity in CAD will be achieved, enabling the identification of disease-specific monocyte subtypes. This could offer new opportunities for improving the diagnosis and treatment of CAD.